Sosialisasi Bahaya Judi Online dengan Prinsip Syariah di Desa Perkebunan Gunung Melayu - Akhmad Shandy; Pani Akhiruddin Siregar (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2025)
The Community Service Program (KKN) is a form of student community service aimed at helping resolve social problems. This research focuses on publicizing the dangers of online gambling (judol), a global phenomenon that causes moral, economic, and social harm, by integrating it with Sharia principles in Perkebunan Gunung Melayu Village. The method used was Participatory Action Research (PAR) with a qualitative approach. The 13-day program involved initial observation, educational-participatory socialization interventions that emphasized the prohibition of Maisir and its relationship to Maqāṣid al-Sharīʿah (Objectives of Sharia), and impact evaluation. The implementation results demonstrated high community enthusiasm and a significant increase in cognitive awareness and understanding of Sharia as a spiritual bulwark against online gambling practices. Furthermore, supporting activities such as mutual cooperation (gotong royong) successfully revitalized the spirit of collaboration and social participation. Despite time constraints and weather constraints, the entire KKN program successfully had a transformative impact, strengthening the community's religious and social values. This study recommends the need for continued monitoring and mentoring to ensure the sustainability of the awareness that has been formed.